“Marriage is Scary” on TikTok: Maqāṣid al-Sharī'ah's Analysis of the Fear of Marriage in the Digital Era - Sari, Delia Atika; Musyafaah, Nur Lailatul (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2025)
Nowadays, there is a lot of discussion on social media about how "marriage is scary". This has instilled a fear of marriage among young social media activists. Marriage is something that is recommended in Islam among the purposes of maintaining offspring (hifz al-nasl). This study aims to discuss in depth the analysis of maqāṣid al-sharī'ah on the fear of marriage in the trend of "marriage is scary" on social media. This research is a field study, specifically focusing on social media, with a case approach related to the trend of "marriage is scary". Primary data were collected from social media platforms, including TikTok and Instagram, while secondary data were sourced from books and journals that discuss marriage and maqasid al-shari'ah. The data was analyzed descriptively using a deductive mindset. This study shows that the content of "marriage is scary" is closely related to the fear of getting married due to past trauma, fear of losing freedom, worries about toxic relationships, economic pressure, and family intervention. From the perspective of maqāṣid al-sharī'ah, marriage aims to establish a Sakinah family, for the benefit of caring for offspring (hifz al-nasl). However, getting married requires physical (hifz al-nafs), mental (hifz al-‘aql), and economic readiness (hifz al-mal). If there is no readiness to get married, then there is no compulsion for the person to carry out the marriage to avoid a greater madharat.